Brand power and brand focus as facilitators of relationship quality in the wine sector - da Cunha, N. P.; Loureiro, S. M. C. (5th International Consumer Brand Relationships, Conference proceedings, 2017)
The effectiveness of long-term relationships with business partners has been getting more attention in recent years from both academics and managers. This study explores a dyadic perspective of wine producers and distributors that identified Brand Focus as new sub-construct of Long-term Relationship Sustainability and Brand Power as new sub-construct of Power, employed to describe the Relationship Quality (RQ) between two important players of the market. The main findings highlight contributions made to brand relationships acting as facilitators of RQ in the wine sector